Screening symptoms of depression and suicidal ideation in people with epilepsy using the Beck depression inventory - Salgado,Priscila Camile Barioni (2012)
OBJECTIVE: To measure the severity of symptoms of depression and suicidal ideation in people with epilepsy (PWE) before and after epilepsy surgery using the Beck Depression Inventory (BDI). We aimed to determine the factors associated to depression in PWE. METHODS: PWE, regardless of epilepsy type, seizure type, duration or frequency of seizures, and AEDs were investigated. The sample (n=468) was divided into two groups: pre-operatory (n=346) and pos-operatory (n=122). RESULTS: Before epilepsy surgery female gender, unemployment and high seizure frequency were associated factors for the occurrence of symptoms of depression. After epilepsy surgery, the only factor associated to high level of depression symptoms was the lack of seizure remission. Suicidal ideation was associated to seizure frequency before and after epilepsy surgery. CONCLUSION: Our results confirm the generally held view that depression is common in PWE and provide further insight to the association of depression with certain socio-demographic and seizure-related factors before and after epilepsy surgery.